Chitonaster johannae Koehler 1907 ... - Jangoux, Michel (Zenodo, 2022)
johannae Koehler, 1907, Chitonaster Chitonaster johannae Koehler, 1907: 144; 1908a: 542, pl. 4, figs 32- 37. — Clark 1993: 250. CURRENT STATUS. — Chitonaster johannae Koehler, 1907. TYPE MATERIAL. — Antarctic • 1 syntype; Scottish Antarctic expedition; 62°10’S, 41°20’W; depth 3248 m; MNHN-IE-2014-116. REMARK Four syntypes in the RSM (Ref. 19211431202) (Smalon, Heppell & Watt, 1976). ... : Published as part of Jangoux, Michel, 2022, The type specimens of extant asteroids (Echinodermata) in the Muséum national d'Histoire naturelle of Paris, pp. 259-334 in Zoosystema 44 (11) on page 293, DOI: 10.5252/zoosystema2022v44a11, http://zenodo.org/record/6616817 ...